L'interdisciplinarité sans concession (Collection ATHENA, 2023)
Based on the experience of the French institution of "Les Maisons des sciences de l'homme", this book revitalizes the question of interdisciplinarity through a precise analysis of the obstacles generated by the very structure of the transmission of knowledge, and the varied issues which are related to it. It exposes the promises of an interdisciplinarity in process.